Correction: Roll-to-roll infrared (IR) drying and sintering of an inkjet-printed silver nanoparticle ink within 1 second. Issue 45 (13th October 2015) - Sowade, Enrico; Kang, Hyunkyoo; Mitra, Kalyan Y.; Weiß, Oliver J.; Weber, Jürgen; Baumann, Reinhard R.
Abstract : Correction for 'Roll-to-roll infrared (IR) drying and sintering of an inkjet-printed silver nanoparticle ink within 1 second' by Enrico Sowade et al., J. Mater. Chem. C, 2015, DOI: ; Web:10.1039/c5tc02291f .